Paul's argumentation in Galatians: a Pragma-dialectical analysis - Hietanen, Mika (Library of New Testament studies, 2007)
"Galatians" is a polemical letter which contains a substantial amount of argumentative passages. Paul evidently wanted to persuade by using the best arguments possible to convince his addressees. Using a state-of-the-art method from the discipline of argumentation analysis, Paul's argumentation can be analyzed with a precision that standard exegetical methods cannot provide. The pragma-dialectical method developed in Amsterdam facilitates an analysis which is both descriptive and normative. On the one hand, Paul's argumentation can be described, such as the relationship between premises and conclusions, the structure of the arguments, and features relating to rhetorical strategy. On the other hand, the method makes it possible to evaluate Paul's argumentation against a set of rules for sound reasoning. Fallacies and problematic arguments can be described accurately. The spiritual nature of Paul's matters does not relieve him of rationality, and Paul himself does not argue as if it did. Paul's argumentation is found problematic in several respects.